Directing grammatically irregular Readings In the Holy Quran - الشيخ حسن, فضل (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Most of the ancient and modern studies have agreed on the importance of invoking the Qur’anic readings, and its impact on the Arabic grammar.The views on the Qur’anic readings varied, so the grammarians accepted some of them and rejected some other relying in the protest on standards that they extrapolated from the words of the Arabs.Hence the need to defend these readings, and reveal the truth of the positions of grammarians, and the beginning was in the books of protest in the fourth century AH. We talked about directing Quranic readings, defining them, and the conditions and criterias that we adopt when invoking reading, then about choice, and is it optional for the reader? And why the choices of some readers were not taken into consideration? We argued for the individual readings first, and then for theaudiencereading. Then we talked about our evaluation of the readings, where we won some of the readings that were rejected by the grammarians on the pretext that they violated the grammatical rules and the writing of the Qur’an.